High Order Thinking Skill (HOTS) based Learning Module Design: Study at Youth Sub-Level I Sunday School/Evangelism Shoots - Nicolaas Saul Rampisela; Christiana Demaja Sahertian; Yance Zadrak Rumahuru (PT FORMOSA CENDEKIA GLOBAL, 2022)
The concept of teaching materials applied to Sunday Schools/Evangelism Buds has not yet adopted the concept of HOTS-based education. The teaching materials used are still based on LOTS (Lower Order Thinking Skills). This is clearly seen from the General Instructional Objectives and Special Instructional Objectives which still use operational words to explain, know and explain. For this reason, this research was conducted, namely to produce HOTS-based learning modules in stimulating interest in learning in Sunday School children, Sub-Level Youth I Congregation of GPM Imanuel OSM Ambon. The researcher developed a learning product in the form of a Sunday School Teen Class learning module with research steps referring to Borg and Gail (1981). In this study, researchers succeeded in producing a product in the form of a HOTS-oriented learning module that can increase students' thinking levels, and produce a learning module product that is used by caregivers in the teaching and learning process for adolescents at SMTPI sub-level 1.